Conjugation and Deconjugation of Ubiquitin Family Modifiers Subcellular Biochemistry - Groettrup, Marcus; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
To cope with the steadily growing body of knowledge and for organizational reasons the articles in this book are focussed on the modifiers ubiquitin, SUMO1/2/3, NED 8, ISG15 and FAT10 but it should be at least mentioned here that enzymes involved in conjugation and deconjugation of URM1, UFM1, ATG8 and ATG12 have been reported and continue to be investigated.
Activation of Ubiquitin and Ubiquitin-Like Proteins -- Control of Ubiquitin Conjugation by Cdc48 and Its Cofactors -- Regulation of Ubiquitin Receptors by Coupled Monoubiquitination -- Control of Cullin-Ring Ubiquitin Ligase Activity by Nedd8 -- Control of Deneddylation by the COP9 Signalosome -- Mechanism, Specificity and Structure of the Deubiquitinases -- Ubiquitin Conjugation and Deconjugation in NF-?B Signaling -- Functions of Linear Ubiquitin Chains in the NF-?B Pathway -- Assembly of K11-Linked Ubiquitin Chains by the Anaphase-Promoting Complex -- Ubiquitin Family Members in the Regulation of the Tumor Suppressor p53 -- Ubiquitylation in the ERAD Pathway -- Pupylation -- Sumo Control -- The In Vivo Functions of Desumoylating Enzymes -- Regulatory Functions of Ubiquitin and SUMO in DNA Repair Pathways -- Sumoylation as a Signal for Polyubiquitylation and Proteasomal Degradation -- In Vivo Functions of Isgylation -- Identification and Validation of ISG15 Target Proteins -- FAT10.
Keywords: Medicine; Biomedicine; Molecular Medicine